Conquering mount diabetes: the highest peak in India - Panchagnula, Neha Bharadwaj (International Journal Of Community Medicine And Public Health, 2017)
The term diabetes has come into colloquial usage over time. As the day passes by, we have more people being diagnosed and more people facing complications. How the silent killer is creeping its way into the world is a known thing. Are all our task forces ready to face the end result? Though we have enough research and supportive facilities, the provider-consumer distance in a developing country like India is a transparent issue. Bolstering the team dynamics and a well-structured team approach right from the primary care provider’s level, might offer us a solution for all that we are facing today.